Clinical placement in Jordan: qualitative views of final year nursing students - Shoqirat, N.; Abu-Qamar, Ma'en (Australian Nursing Federation, 2013)
Objective: This study explored the nurse student’s experience of the final year placement, and uncovered contributing factors to a positive clinical experience in Jordan. Design: A qualitative explorative approach was used. Two focus group discussions were conducted in Arabic language with a total of 12 participants selected randomly from the list of students who completed the period of pre-graduation intensive clinical placement. The focus discussions were digitally recorded. Setting: The setting for this study was a public faculty of nursing located in the southern province, Jordan. Subjects: Twelve final year nursing students including seven males and five females took part in the study. Main outcomes measures: The recorded discussions were translated independently into English text and were uploaded into Nvivo 9 for thematic analysis. Results: Three themes emerged from the data. The first theme related to the environment of clinical placement and included two sub-themes: ‘from orientation-to-team work‘ and ‘from tiredness-to-ignorance’. The second theme is about the faculty and preceptors as reflected by the lack of coordination between the clinical settings and the faculty, plus inconsistency in students’ evaluation. The third theme concerned patient preferences that included a lack of interest in receiving care from students. Conclusion: Creating a supportive learning environment guided by issues identified and implications put forward by this research is a prerequisite for successfully executed nursing programs. Failure to do so could lead to a stressful transitional journey and detachment from the classroom and the real world of clinical work.